KAPASITAS PERANGKAT DESA DALAM PENYELENGGARAAN ADMINISTRASI PEMERINTAHAN DESA - Sri Untari; M. Mujtaba Habibi; Abd Mu'id Aris Shofa; Lia Nurul Fauziah; Aliyah Ardhana Riswari (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2022)
The purpose of this study is to analyze the capacity of village apparatus in the management of village government administration in a case study in Boro Village, Selorejo District, Blitar Regency. This research approach is qualitative with the type of case study research. The data sources are obtained from informants, events, and documents. Data were collected by interview, observation, and documentation techniques. Data analysis was carried out with a case study recommended by Yin with pattern matchmaking. The results of the study show that the capacity of village officials in implementing village administration as seen from: (1) conceptual mastery is not optimal. This is due to the education level of the apparatus which is still low on average high school; minimal training experience, (2) technical skills are not optimal, caused by limited facilities, no wifi, not yet mastered applications, and lack of skills in using information technology in managing village government administration, (3) social skills are good, this becomes social capital valuable in village governance.Tujuan kajian ini untuk menganalisis kapasitas aparatur desa dalam manajemen administrasi pemerintahan desa studi kasus di Desa Boro, Kecamatan Selorejo Kabupaten Blitar. Pendekatan penelitian ini kualitatif dengan jenis penelitian studi kasus.Sumber data diperoleh dari informan, peristiwa dan dokumen. Data dikumpulkan dengan teknik wawancara, observasi dan dokumentasi. Analisis data dilakukan dengan studi kasus yang direkomendasi Yin dengan penjodohan pola. Hasil kajian menunjukkan hasil yaitu kapasitas aparat desa dalam pelaksanaan administrasi pemerintahan desa yang dilihat dari: (1) penguasaan konseptual belum optimal. Hal ini disebabkan oleh tingkat pendidikan aparat yang masih rendah rata2 SMA; pengalaman pelatihan yang minim, (2) keterampilan teknis belum optimal, yang disebabkan oleh terbatasnya sarana, belum ada wifi, belum dikuasainya aplikasi dan kurangnya keterampilan dalam penggunaan teknologi informasi dalam pengelolaan administrasi pemerintahan desa, (3) kecakapan sosial sudah bagus, ini menjadi modal sosial yang berharga dalam pemerintahan desa.